Diagnostic accuracy of hysterosalpingography and laparoscopy in tubal patency - Banotra, Palvi; Ahmad, Zahoor (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: There is no doubt that health care providers face a great deal of challenge to deal with the infertility issue, a serious and tragic gynecological problem encountered in developing countries. Laparoscopy is considered as the gold standard for assessment of tubal factors of infertility, although because of its invasive nature, cost and the need for anaesthesia and hospitalization, HSG seems to be a basic routine procedure for tubal factors. Hence, the present study was designed to compare the accuracy of HSG with SSG for evaluation of tubal factor infertility. Laparoscopy is considered as the gold standard for assessment of tubal factors of infertility, although because of its invasive nature, cost and the need for anaesthesia and hospitalization, HSG seems to be a basic routine procedure for tubal factors. Currently with the availability of the ultrasonography machines with very good resolution, SSG can be simultaneously practiced with ultrasonography during day 7-9 of the menstrual cycle to assess tubal patency. Hence, the present study was designed to compare the accuracy of HSG with laparoscopyfor evaluation of tubal factor infertility. Methods: The present prospective study on the diagnostic accuracy of hysterosalpingography (HSG) in the evaluation of infertility due to tubal patency has been conducted at Lala-Ded Hospital, Srinagar from September 2015 to February 2016. All the patients with infertility having regular menses, normal male partner with semen analysis and aging 20-30 years old have been included in the study. However, females who underwent HSG previously, case of unovulation despite clomiphene citrate, acute PID, salpingectomy, endometriosis, past history of oophorectomy and women beyond 35 years of age have been excluded in this study. Results: The average age of patients was observed as (26.7±4.81) years with majority of patients belonging to (25-29) year age group. We performed sensitivity analysis of HSG procedure by taking laparoscopic findings as gold standard; evidently, we found the sensitivity and specificity of HSG as 91.3% and 88.9% respectively. Interestingly, the diagnostic accuracy of HSG was observed as 89.7%. Conclusions: We found that HSG has satisfactory predictive value in identifying the factor of infertility. Laparoscopy is still a gold standard but if the purpose is attained with minimally invasive and cost-effective procedure having a good accuracy rate then over diagnosis should be avoided.